2014
DOI: 10.5296/ijafr.v4i2.6482
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trade Openness, FDI, Exchange Rate and Inflation on Economic Growth: A Case Study of Pakistan

Abstract: This study focuses on empirical analysis to find out the role of trade openness, inflation, imports, exports, real exchange rate and foreign direct investment in enhancing economic growth in Pakistan. The analysis based on time series data for the period 1980 to 2011. This paper uses ADF; PP and DF-GLS tests to find out stationarity of the variables and Co-integration and DOLS (Dynamic Ordinary Least Square) techniques have been used for the estimation. Co integration results indicated the long run relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
28
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 9 publications
12
28
1
3
Order By: Relevance
“…Sayek (2009) suggest using investment-smoothing possibility from FDI to reduce the real negative effects of inflation. The results from this research do not deviate much from existing literature, the hypothesis of the existence of a co-integration relationship in the long run among variables is accepted similarly in the findings of Dorantes & Pozo (2001), Bibi et al, (2014), Simionescu (2016), and Kueh & Yong (2018). Besides that, the long-run causality relationship between REER, Inflation, and GDP towards FDI is consistent with the results of Amoah et al, (2015).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Sayek (2009) suggest using investment-smoothing possibility from FDI to reduce the real negative effects of inflation. The results from this research do not deviate much from existing literature, the hypothesis of the existence of a co-integration relationship in the long run among variables is accepted similarly in the findings of Dorantes & Pozo (2001), Bibi et al, (2014), Simionescu (2016), and Kueh & Yong (2018). Besides that, the long-run causality relationship between REER, Inflation, and GDP towards FDI is consistent with the results of Amoah et al, (2015).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, inflation has been hypothesized to distort the tax system that would, in turn, discourage investors for the long run due to money illusion (Omankhanlen, 2011). Furthermore, Bibi et al (2014) show that there is a long-run relationship between the variables. The inflation rate is negatively related to economic growth.…”
Section: Introductionmentioning
confidence: 93%
“…In Bangladesh, Adhikary [41] explored the relationship among FDI, trade openness, capital formulation, and economic growth, and the results showed that FDI and capital formulation affected the economic growth positively and significantly, while trade openness was adversely linked with economic growth. Another study proposed by Bibi et al [42] explored a negative association between trade openness and economic growth. The outcomes of DOLS cointegration regression indicated that a 1% increase in trade openness would reduce economic growth by 1.091% due to exchange rate depreciation in particular economies.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange rate plays a vital role in a country's level of trade, which is critical to most, or all, free market economies in the world. Its variance is persistent and serially correlated long-term economic growth providing a relationship between interest rate, inflation rate and exchange rate volatility in Malaysia covering the period between 1999 and 2009 (Asari et al, 2011).A study has been done on empirical analysis to find out the role of trade openness, inflation, imports, exports, real exchange rate and foreign direct investment in enhancing economic growth in Pakistan for the period 1980 to 2011 (Bibi, 2014). This study concluded that a similar effect would take place on trade imbalance and the stock market, as some have already asserted.…”
Section: Outsourcing and Us Industriesmentioning
confidence: 99%